Sales Growth, Profitability, Inventory Intensity and Capital Structure on Tax Aggressiveness in Energy Sector in Indonesia - Irawati, Wiwit; Kurniasih, Lisna; Barli, Harry (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2025)
This study examines the effect of Sales Growth, Profitability, Inventory Intensity, and Capital Structure on Tax Aggressiveness. The results indicate that, simultaneously, Sales Growth, Profitability, Inventory Intensity, and Capital Structure have a significant impact on Tax Aggressiveness. However, when analyzed individually, Sales Growth, Profitability, and Inventory Intensity do not significantly affect Tax Aggressiveness. In contrast, Capital Structure has a positive and significant effect on Tax Aggressiveness. The population for this study consists of 74 companies, with a sample size of 105 data points from 21 energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period, using a purposive sampling technique. The data analysis was conducted using descriptive statistics and panel data regression analysis through the EViews application.